Principles and philosophies for speech and language therapists working with people with primary progressive aphasia: an international expert consensus. Issue 6 (13th March 2023) - Volkmer, A.; Cartwright, J.; Ruggero, L.; Beales, A.; Gallée, J.; Grasso, S.; Henry, M.; Jokel, R.; Kindell, J.; Khayum, R.; Pozzebon, M.; Rochon, E.; et al.
Abstract: Purpose: Primary progressive aphasia (PPA) is a language-led dementia associated with Alzheimer's pathology and fronto-temporal lobar degeneration. Multiple tailored speech and language interventions have been developed for people with PPA. Speech and language therapists/speech-language pathologists (SLT/Ps) report lacking confidence in identifying the most pertinent interventions options relevant to their clients living with PPA during their illness trajectory. Materials and methods: The aim of this study was to establish a consensus amongst 15 clinical-academic SLT/Ps on best practice in selection and delivery of speech and language therapy interventions for people with PPA. An online nominal group technique (NGT) and consequent focus group session were held. NGT rankings were aggregated and focus groups video recorded, transcribed, and reflexive thematic analysis undertaken. Results: The results of the NGT identified 17 items. Two main themes and seven further subthemes were identified in the focus groups. The main themes comprised (1) philosophy of person-centredness and (2) complexity. The seven subthemes were knowing people deeply, preventing disasters, practical issues, professional development, connectedness, barriers and limitations, and peer support and mentoring towards a shared understanding. Conclusions: This study describes the philosophy of expert practice and outlines a set of best practice principles when working with people with PPA. Implications for rehabilitation: Primary progressive aphasia (PPA) describes a group of language led dementias which deteriorate inexorably over time. Providing speech and language therapy for people with PPA is complex and must be person centred and bespoke. This study describes the philosophy of expert practice and outlines a set of best practice principles for speech and language therapists/pathologists working with people with people with PPA.